2020
DOI: 10.3390/ijms22010265
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Immunomodulatory Benefits of Taro (Colocasia esculenta) Corms, an Underexploited Tuber Crop

Abstract: Taro corms contain valuable bioactive molecules effective against cancer and cancer-related risk factors, such as carcinogens and biological agents, several pathophysiological conditions, including oxidative stress and inflammation, while controlling metabolic dysfunctions and boosting the immunological response. Such broad effects are achieved by the taro health-influencing compounds displaying antitumoral, antimutagenic, immunomodulatory, anti-inflammatory, antioxidant, anti-hyperglycemic, and anti-hyperlipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 126 publications
1
24
0
2
Order By: Relevance
“…It can be found within the range of 1 to 1000ppm and can cause harmful adverse effects on the consumers. This data was supported by National Toxicology Program (NTP) and confirmed the presence of cancer-causing carcinogen in these food stuffs [74,75]. The different types of malignancy associated with particular carcinogens are enlisted in Fig.…”
Section: Effect Of Cooking Methods On Formation Of Carcinogenssupporting
confidence: 63%
“…It can be found within the range of 1 to 1000ppm and can cause harmful adverse effects on the consumers. This data was supported by National Toxicology Program (NTP) and confirmed the presence of cancer-causing carcinogen in these food stuffs [74,75]. The different types of malignancy associated with particular carcinogens are enlisted in Fig.…”
Section: Effect Of Cooking Methods On Formation Of Carcinogenssupporting
confidence: 63%
“…Taro corm is a tubercle traditionally consumed in Asia, West African countries, the USA, Canada, Japan, Turkey, and Central and South America countries, where it is considered and used as a food with medicinal effects to treat several physiopathological conditions through immune response stimulation to restore health status. Many studies have proven that taro corms contain several bioactive molecules, corroborating popular knowledge and its applied medicinal purposes [1,5,40,41]. Tarin is included among these bioactive molecules and has been extensively studied for over 15 years.…”
Section: Discussionmentioning
confidence: 89%
“…Taro corms are a significant source of carbohydrates, followed by dietary fibers, proteins, vitamins such as folates, niacin, pantothenic acid, pyridoxin, riboflavin, thiamin, vitamin A, C, E, and K, and minerals including calcium, copper, iron, magnesium, manganese, selenium, and zinc [4]. In addition to their nutritional value, taro corms are rich in bioactive compounds such as tarin, taro-4-I polysaccharide, TPS1/TPS2 polysaccharides, A-1/B-2 α-amylase inhibitors, monogalactosyldiacylglycerols (MGDGs), digalactosyldiacylglycerols (DGDGs), polyphenols, and nonphenolic antioxidants that are responsible for antitumoral, anti-metastatic, anti-mutagenic, immunomodulatory, anti-inflammatory, antioxidant, anti-hyperglycemic, and anti-hyperlipidemic activities, supporting their ancient 2 of 14 application for medicinal purposes by indigenous people and, thus considered a functional food [1,5].…”
Section: Introductionmentioning
confidence: 92%
“…The bioactive compounds of taro have antitumor, antimutagenic, immunomodulatory, antiinflammatory, antioxidant, antihyperglycemic and antihyperlipidemic activities. Ribeiro et al (2021) reported that the bioactivity of taro tuber is attributed to the combination of tarin, taro polysaccharide-4-I, taro polysaccharides 1 and 2 (TPS-1 and TPS-2), A-1/B-2 α-amylase inhibitors, monogalactosyldiacylglycerols (MGDGs), digalactosyldiacylglycerols (DGDGs), polyphenols and non-phenolic antioxidants and provide anticancer and immunomodulatory benefits.…”
Section: Productive Performancementioning
confidence: 99%